Analisis Dampak Covid-19 Terhadap Praktik Bisnis UMKM di Kabupaten Sikka - Fransiskus De Romario; Pipiet Niken Aurelia; Theodora Heldayana Ine Weni (Jurnal Ilmiah Wahana Pendidikan, 2021)
Micro, Small and Medium Enterprises (MSMEs) are the most strategic national economic sectors and concern the livelihoods of many people so that they become the backbone of the national economy. Data collection methods are techniques or methods that can be used by researchers to collect data, and data collection instruments are tools selected and used by researchers in their activities to collect data so that these activities become systematic and easier. The results of the Covid-19 pandemic research have made many sectors slump, including the MSME sector in Sikka Regency. The impact of Covid-19 has made MSME actors experience a decrease in income, difficulties in capital turnover, disruption to the distribution of goods, difficulties in obtaining raw materials and also in human resources. The MSME sector in Sikka Regency that was most affected during the Covid-19 pandemic included the culinary field, the beauty sector, the grocery store sector, the handicraft product sector, the agribusiness sector and the lodging sector